Seroprevalence of Epstein-Barr virus infection in children during the COVID-19 pandemic in Zhejiang, China - Fengqing Cai; Hui Gao; Qing Ye (Frontiers Media S.A., 2023)
AimWe aimed to investigate the seroprevalence of Epstein-Barr virus (EBV) infection in children before and during the COVID-19 pandemic.MethodsAll children admitted to the Children's Hospital Affiliated to Zhejiang University from January 2019 to December 2021 with suspected EBV-associated disease and EBV antibodies were detected by a two-step indirect method of chemiluminescence technology. A total of 44,943 children were enrolled in this study. The seroprevalence of EBV infections was compared from January 2019 to December 2021.ResultsThe total seropositive rate of EBV infections was 61.02% between January 2019 and December 2021, and the seropositive trend decreased year by year. The total number of seropositive EBV infections in 2020 was reduced by 30% compared to that in 2019. In particular, nearly 30% and 50% reductions in the number of acute EBV infections and EBV reactivations or late primary infections from 2019 to 2020 were found, respectively. The number of acute EBV infections in children aged 1-3 years and EBV reactivation or late primary infection in children aged 6-9 years in 2020 sharply dropped by approximately 40% and 64% compared to that in 2019.ConclusionsOur study further demonstrated that the prevention and control measures for COVID-19 in China had a certain effect on containing acute EBV infections and EBV reactivations or late primary infections.